Cellular Therapy in High-Risk Relapsed/Refractory Chronic Lymphocytic Leukemia and Richter Syndrome - Barbanti, Maria Chiara; Appleby, Niamh; Kesavan, Murali; Eyre, Toby Andrew (Frontiers in Oncology, 2022)
Despite the development of highly effective, targeted inhibitors of B cell proliferation and anti-apoptotic pathways in chronic lymphocytic leukemia (CLL), these treatments are not curative, and many patients will develop either intolerance or resistance to these treatments. Transformation of CLL to high grade lymphoma – so called Richter syndrome (RS) – remains a highly chemoimmunotherapy-resistant disease, with transformation occurring following targeted inhibitors for CLL treatment being particularly adverse. In light of this, cellular therapy in the form of allogenic stem cell transplantation and chimeric antigen receptor T cell therapy continues to be explored in these entities. We review the current literature assessing these treatment modalities in both high risk CLL and RS. We also discuss their current limitations and place in treatment algorithms.